Efektivitas Quick Response Code Indonesian Standard (QRIS) Dipasar Atas Kota Bukittinggi Ditinjau Dari Ekonomi Islam - Tesya Elma Putri; Gusril Basir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
QRIS is a non-cash payment instrument in the form of a QR code developed by Bank Indonesia and the Indonesian Payment Association. With the existence of QRIS, Bank Indonesia hopes to facilitate public transactions and not be left behind by technology. As a Muslim community, especially in Pasar Atas, Bukittinggi, we must understand how the law uses QRIS. because everything we do must be based and not deviate from the teachings of Islam. The aim of this research is to find out how the effectiveness of using the Quick Response Code Indonesian Standard (QRIS) in buying and selling transactions at Pasar Atas Kota Bukittinggi is viewed from an Islamic economic perspective. This type of research is a qualitative descriptive method by collecting data through interviews with traders and buyers who shop at Pasar Atas Kota Bukittinggi. The results of this study indicate that QRIS users receive many benefits, such as facilitating transactions, not having difficulty finding small money, reducing the spread of counterfeit money, not reducing the value of money and there are still many benefits received by QRIS users. Therefore it can be said that QRIS is more effective.